Evaluation of autophagy inhibition to combat cancer: (vanadium complex)-protein interactions, parameterization, and validation of a new force field - Santos, Taináh M R; Tavares, Camila A; Pereira, Ander F; da Cunha, Elaine F F; Ramalho, Teodorico C (Journal of molecular modeling, 2023)
Autophagy has drawn attention from the scientific community, mainly because of its significant advantages over chemotherapeutic processes. One of these advantages is its direct action on cancer cells, avoiding possible side effects, unlike chemotherapy, which reaches tumor cells and affects healthy cells in the body, leading to a great loss in the quality of life of patients. In this way, it is known that vanadium complex (VC) [VO(oda)(phen)] has proven inhibition effect on autophagy process in pancreatic cancer cells. Keeping that in mind, molecular dynamics (MD) simulations can be considered excellent strategies to investigate the interaction of metal complexes and their biological targets. However, simulations of this type are strongly dependent on the appropriate choice of force field (FF). Therefore, this work proposes the development of AMBER FF parameters for VC, having a minimum energy structure as a starting point, obtained through DFT calculations with B3LYP/def2-TZVP level of theory plus ECP for the vanadium atom. An MD simulation in vacuum was performed to validate the developed FF. From the structural analyses, satisfying values of VC bond lengths and angles were obtained, where a good agreement with the experimental data and the quantum reference was found. The RMSD analysis showed an average of only 0.3%. Finally, we performed docking and MD (120 ns) simulations with explicit solvent between VC and PI3K. Overall, our findings encourage new parameterizations of metal complexes with significant biological applications, as well as allow to contribute to the elucidation of the complex process of autophagy.
Keywords: nádory; simulace molekulární dynamiky; Docking; Humans; Vanadium; Coordination Complexes; Autophagy; Molecular dynamics; lidé; Neoplasms; komplexní sloučeniny; Molecular Dynamics Simulation; autofagie; vanad; Vanadium complex; kvalita života; Quality of Life; AMBER force field